TREATMENT OF D-GALACTOSE INDUCED MOUSE AGING WITH LYCIUM BARBARUM POLYSACCHARIDES AND ITS MECHANISM STUDY - Tang, Tao; He, Bixiu (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
We evaluated the effects of Lycium barbarum polysaccharides LBP)on D-galactose aging model mouse and explored its possible mechanism. Kunming mice were randomly divided into the control group, the model group, the high-dose LBP group, and the low-dose LBP group. Except the control group, D-galactose was used for modelling. The drug was administrated when modelling, mouse behavioural, learning and memory changes were observed, and the contents of lipid peroxidation (LPO), lipofuscin (LF) and monoamine oxidase B (MAO-B) in mouse brain tissue and the weight of immune organs were measured after 6 weeks. Compared with the control group, mouse weight gain in the model group reduced significantly. Compared with model group, after mice drank LBP, the times of electric shock was less than aging mice (in which, the high-dose LBP group, P<0.05), and electric shock incubation period was longer (P<0.01). On Day 45 after modelling and drug administration, the contents of LPO, LF and MAO-B in mouse brain tissue in the model group increased significantly, while those in the drug administration groups decreased significantly. The thymus index in the aging model group decreased significantly; the thymus index and the spleen index in the high-dose LBP group and the low-dose LBP group rebounded significantly (P<0.01). We concluded that LBP has an anti-aging effect on D-galactose induced aging model mouse, and its mechanism may be related with the alleviation of glucose metabolism disorder and the resistance of the generation of lipid peroxide and other substances, which damage cell membrane lipid.